Nursing‐Led Models of Tracheostomy Management for Patients With Head and Neck Cancer: A Mixed‐Methods Study - Sarah Davies; Carsten Palme; Faruque Riffat; Emma Charters (Journal of Clinical Nursing, 2026)
ABSTRACT Background The incidence of head and neck cancer (HNC) is rising globally, with patients undergoing extensive surgical resection for advanced disease frequently requiring prophylactic tracheostomy to secure the airway in the early postoperative period. Specialised HNC nurses undertake extended scope tracheostomy procedures, including tube changes and decannulations, yet practice varies widely between institutions and no standardised training framework exists. Aims and Objectives To benchmark the roles and responsibilities of specialised HNC nurses in tracheostomy management across Australia, and to explore the facilitators, barriers and enablers of nurse‐led extended practice. Design National mixed‐methods study. Methods An online REDCap questionnaire was distributed to nurses with inpatient HNC tracheostomy experience within the past 5 years ( n = 22). A subset participated in semi‐structured interviews ( n = 11), analysed using inductive thematic analysis. Results Most participants were senior metropolitan‐based nurses with over 12 years of HNC experience. Nine (41%) performed tracheostomy tube changes and 14 (64%) conducted decannulations. Thematic analysis identified six themes: the central role of the multidisciplinary team; education and patient support; training and skill acquisition; extended scope of practice; challenges to nurse‐led management; and benefits of nurse‐led management. Skill acquisition was facilitated by mentoring and high‐volume exposure; barriers included collegial resistance, equipment access and workload pressures. Conclusions Specialised HNC nurses report undertaking extended scope tracheostomy procedures across a range of Australian centres, with mentoring, high‐volume clinical exposure and multidisciplinary collaboration described as key enablers. Standardised competency frameworks may help to reduce inter‐institutional variation; however, the safety, efficiency and patient‐level outcomes of these models were not directly evaluated in this study and warrant formal investigation in future research. Relevance to Clinical Practice This study provides the first national descriptive data on the role of nurses in tracheostomy management for patients with HNC in Australia and offers a foundation for the development of standardised training pathways. The potential impact of such pathways on efficiency, length of stay and nursing workforce capacity warrants formal evaluation in future studies.